ULAMA PEREMPUAN INDONESIA: RESISTENSI TERHADAP KONSTRUKSI SOSIAL PATRIARKI - Muhammad Chabibi (Asketik : Jurnal Agama dan Perubahan Sosial, 2021)
This paper aims to explain the position and role of Indonesian Women's Ulama in responding to the socialproblems of women in the patriarchal culture of Ulamā’ which is dominated by male Ulamā’ in Indonesia. UsingPeter L.Berger and Luckmann's (1966) social construction theory, this paper seeks to explore the capacity ofIndonesian Women’s Ulama in solving socio-religious problems, especially in the field of female law and socialissues in Indonesia. Law-making in Indonesia cannot be separated from the patriarchal construction built bythe intellectual hegemony of male Ulamā’ (Islamic scholars) and the existence of social inequality betweenmen and women in the dominance of social interpretations which results in the dominance of masculinity inthe public sector. This paper uses qualitative research methods with data collection techniques in the form ofobservation and documentation. The conclusions of this paper are 1) the intellectual ahistorism of women sociallyconstructed through verbalization, visualization, and adaptation in the socio-cultural scientific tradition; 2) thecultural backwardness experienced by women when men step forward in their socio-cultural intellect in thepublic sector such as law, education, politics and economics.